Hereditary spastic paraplegia due to NIPA1 gene mutation: Case report - Dary Jizeth Parra-Párraga; Eugenia Espinosa-García (Case Reports)
Introduction: Hereditary spastic paraplegia (HSP) is the term for a group of neurological disorders characterized by progressive spasticity and muscle weakness in the lower limbs. Its etiology is genetic and has been associated with mutations in more than 60 genes. HSP is rare and may be useful in the differential diagnosis of cerebral palsy.